2004
DOI: 10.3732/ajb.91.3.449
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic classification of peltigeralean fungi (Peltigerales, Ascomycota) based on ribosomal RNA small and large subunits

Abstract: To provide a comprehensive molecular phylogeny for peltigeralean fungi and to establish a classification based on monophyly, phylogenetic analyses were carried out on sequences from the nuclear ribosomal large (LSU) and small (SSU) subunits obtained from 113 individuals that represent virtually all main lineages of ascomycetes. Analyses were also conducted on a subset of 77 individuals in which the ingroup consisted of 59 individuals representing six families, 12 genera, and 54 species potentially part of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
96
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 111 publications
(107 citation statements)
references
References 52 publications
(112 reference statements)
9
96
0
1
Order By: Relevance
“…In a traditional circumscription the members of the Collemataceae were also characterized by a similar ascoma development, a disc-shaped proper wall (exciple), and asci with an internal amyloid tube structure (Henssen, 1965;Henssen, 1981 Degelius, 1954). This was also supported by several early studies of Peltigerales phylogeny, where the included Collema and Leptogium representatives did not form monophyletic groups (Wiklund and Wedin, 2003;Miadlikowska and Lutzoni, 2004;Wedin and Wiklund, 2004; Miadlikowska et al, 2006). Two recent studies focussing more specifically on Collemataceae in the old, wide sense confirmed this reciprocal non-monophyly (Wedin et al, 2009; Otálora 6 et al, 2010), which was also supported by later studies on Peltigerales (Muggia et al, 2011;Spribille and Muggia, 2012).…”
supporting
confidence: 59%
“…In a traditional circumscription the members of the Collemataceae were also characterized by a similar ascoma development, a disc-shaped proper wall (exciple), and asci with an internal amyloid tube structure (Henssen, 1965;Henssen, 1981 Degelius, 1954). This was also supported by several early studies of Peltigerales phylogeny, where the included Collema and Leptogium representatives did not form monophyletic groups (Wiklund and Wedin, 2003;Miadlikowska and Lutzoni, 2004;Wedin and Wiklund, 2004; Miadlikowska et al, 2006). Two recent studies focussing more specifically on Collemataceae in the old, wide sense confirmed this reciprocal non-monophyly (Wedin et al, 2009; Otálora 6 et al, 2010), which was also supported by later studies on Peltigerales (Muggia et al, 2011;Spribille and Muggia, 2012).…”
supporting
confidence: 59%
“…P. membranacea is a cyanolichen, with Nostoc cyanobacteria as photobiont (Miadlikowska & Lutzoni, 2004). A metagenomic library was constructed from a collection of lichen thalli and the bacterial microbiota were analysed in terms of phylogenetic diversity and functional gene composition.…”
Section: Introductionmentioning
confidence: 99%
“…The most common type of cyanobacterial lichen photobiont is Nostoc (Nostocaceae) (Antoine, 2004;Nash, 2008a), which is the symbiont associated with members of the lichen-forming fungal genus Peltigera (Tschermak-Woess, 1988;Miadlikowska & Lutzoni, 2004;O'Brien et al, 2005;Hodkinson et al, 2012a), the group that is the focus of our research (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%